Pengaruh Pola Komunikasi Keluarga dalam Fungsi Sosialisasi Keluarga terhadap Perkembangan Anak - A. Sari; A.V.S. Hubeis; S. Mangkuprawira; A. Saleh (Jurnal Komunikasi Pembangunan, 2010)
This research explain that the family communications pattern analysis, function of socialization of family, form ofcommunication happened at family who live in setlement and countrified in Bekasi City. Besides, also to knowdevelopment of child of of the the family. Method which in using in this research is descriptive method usesdescriptive survey design, data analysis Statistik by using Lisrel version 8.70. Result of research indicates thatcommunications pattern to family in setlement is more usingly is combination pattern between patterns laisez-faire,protektif, pluralistik, and konsensual. Its use in corresponding to various conditions and situation when mothering.Function of active socialization, passive and radical in using in combination by family who live in setlement andcountrified. In mother tongue usage ( area), both types of the family applies for inuring and recognition to child ofchild of they.